2012
DOI: 10.2478/v10111-012-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Treści z zakresu ochrony przyrody w edukacji leśnej społeczeństwa / Nature protection issues in forestry related education of the society

Abstract: The State Forests -National Forest Holding protects, utilizes and shapes Poland's public forests over an area exceeding 7.5 million hectares. Apart from these tasks, it undertakes the forestry education of the society. Today, about 1.5-2 million people benefit every year from the educational activities offered by the State Forests. These are mainly financed by the State Forests organisational units' themselves. Nature protection is an essential aspect of the society's forestry education. It should include both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Stąd ich mnogość w potrawach o charakterze obrzędowym, spożywanych chociażby w Wigilię 65 . Nie odnotowano natomiast popularnego w innych regionach przekonania o tym, że sen o grzybach zwiastuje nieszczęście 66 , informatorzy nie pamiętali także o obowiązku rytualnego obmycia po zakończonym zbiorze 67 lub zakazie grzybobrania przez kobiety w ciąży 68 . Nie wymienili wróżb agrarnych.…”
Section: Zbieractwounclassified
“…Stąd ich mnogość w potrawach o charakterze obrzędowym, spożywanych chociażby w Wigilię 65 . Nie odnotowano natomiast popularnego w innych regionach przekonania o tym, że sen o grzybach zwiastuje nieszczęście 66 , informatorzy nie pamiętali także o obowiązku rytualnego obmycia po zakończonym zbiorze 67 lub zakazie grzybobrania przez kobiety w ciąży 68 . Nie wymienili wróżb agrarnych.…”
Section: Zbieractwounclassified
“…Its introduction is carried out in the direction of fulfilling the international obligation to provide social and environmental tasks in addition to economic tasks [1][2][3]. As a result of a review of existing studies [4][5][6][7][8], it can be concluded that attempts have been made to conduct a very broad dialogue; however, there are no in-depth studies on the use of social media in communication between groups of communities involved in the production of forest products and the public. The relevance of research on the role of social media in the relationship between forest producers and Polish society is evidenced by activities highlighting the need for new forms of education, contact and even discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred form of education was classes conducted in forest areas with educators [21]. According to Referowska-Chodak, Hattie et al, and Becler et al [22][23][24], for educational activities to bring the desired effects in changing the perception of forest management and the adoption of appropriate environmental attitudes, they must be conducted regularly, preferably in the natural environment [25,26]. Unfortunately, the reports on educational activities in National Forests do not show whether individuals regularly attended classes or if it was just a one-time activity, and there is also no information about the subject matter of individual classes, including those on climate change.…”
Section: Introductionmentioning
confidence: 99%